Diastereoselective auxiliary- and catalyst-controlled intramolecular aza-Michael reaction for the elaboration of enantioenriched 3-substituted isoindolinones. Application to the synthesis of a new pazinaclone analogue - Romain Sallio (Beilstein Journal of Organic Chemistry, 2018)
A new asymmetric organocatalyzed intramolecular aza-Michael reaction by means of both a chiral auxiliary and a catalyst for stereocontrol is reported for the synthesis of optically active isoindolinones. A selected cinchoninium salt was used as phase-transfer catalyst in combination with a chiral nucleophile, a Michael acceptor and a base to provide 3-substituted isoindolinones in good yields and diastereomeric excesses. This methodology was applied to the asymmetric synthesis of a new pazinaclone analogue which is of interest in the field of benzodiazepine-receptor agonists.